A Comprehensive Review of Ethnomedicinal Uses, Phytochemistry, Pharmacology, and Toxicity of Prunus africana (Hook. F.) Kalkman from Africa - James K. Ndung’u; Joseph M. Nguta; Isaac M. Mapenay; Gervason A. Moriasi (Scientifica)
Prunus africana, a widely utilized medicinal plant in various African ethnic communities, continues to hold significant importance in traditional healing practices. Research has identified phytochemical compounds in this plant, exhibiting diverse pharmacological activities that offer potential for pharmaceutical development. Notably, P. africana is employed in treating various ailments such as wounds, diabetes mellitus, malaria, benign prostatic hyperplasia, chest pain, and prostate cancer. Its pharmacological properties are attributed to a spectrum of bioactive compounds, including tannins, saponins, alkaloids, flavonoids, terpenoids, phytosterols, and fatty acids. Multiple studies have documented the anti-inflammatory, antimicrobial, antiandrogenic, antiangiogenic, antioxidant, antidipeptidyl peptidase-4 activity, analgesic, and astringent properties of P. africana extracts. This review offers a comprehensive compilation of ethnomedicinal applications, phytochemical composition, pharmacological effects, and toxicity assessments of P. africana, serving as a foundation for future preclinical and clinical investigations. By understanding its traditional uses and chemical constituents, researchers can target specific medical conditions with greater precision, potentially expediting the development of safe and effective pharmaceuticals. Moreover, toxicity assessments provide crucial insights into the safety profile of P. africana extracts, ensuring the development of safe pharmaceuticals to treat various diseases.